A flexible 3D printing material with double-layer structure and preparation method thereof
By adopting a double-layer structure design in 3D printing materials, hard TPU cladding and inner flexible TPU composite with high elongation of break, the problem of traditional materials being stuck in AMS systems is solved, and efficient printing of flexible products is achieved.
Patent Information
- Application Number
- CN202411823129.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-12
AI Technical Summary
Traditional hard 3D printing materials are prone to stuck in AMS systems, resulting in the failure of automatic material change and color change functions, and the flexibility and elasticity of flexible products are insufficient.
Flexible 3D printing material with a double-layer structure is adopted to ensure that the material is smoothly replaced in AMS and the printing of flexible products is achieved during FDM printing.
The smooth replacement of 3D printed materials in AMS systems and the good flexibility and elasticity of flexible products printed by FDM are achieved, avoiding the need for additional processing.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of 3D printing materials, and in particular relates to a flexible 3D printing material with a double-layer structure and a preparation method thereof. Background Art
[0002] The fused deposition modeling printer (FDM for short) has an AMS automatic material changing system (referred to as AMS in the present invention) when realizing the automatic color changing and wire changing functions. The system can fully realize the color printing function of hard plastic 3D printing materials (hardness 80D) and above. However, in practical applications, many occasions require the use of flexible materials to manufacture products, especially those application scenarios that require a certain degree of elasticity and bending ability. Although traditional hard materials can meet certain printing requirements, their performance is inadequate when manufacturing products such as soles, sealing rings, pipe joints, etc. that require higher flexibility. Therefore, the introduction of flexible materials has become an inevitable choice. Flexible materials can not only provide the required elasticity and wear resistance, but also allow the printed models to have a smoother and more delicate surface quality.
[0003] The most common 3D printing flexible materials on the market, such as TPU\TPE, are all formed by blending and one-piece extrusion, but this material cannot meet the AMS of 3D printing fused deposition modeling (FDM). The material is easily deformed and stuck in the AMS during the process of being clamped by the gears and dragged by the motor, resulting in the complete failure of the automatic material change and color change functions. In response to this problem, the Chinese invention patent with application number 2015105942418 provides a new type of hard flexible 3D printing material, which first obtains a hard material by adding some hard materials (such as polyvinyl alcohol, polyvinyl butyral, etc.) that can be softened by post-processing methods and hardening components (such as PC, ABS, etc.) to the flexible matrix, and then the model made of 3D printing filaments is softened by soaking in water, vinegar, wine, alkaline solution, or salt water. This not only solves the problems of printing with traditional flexible materials, but also achieves the softness required by the material when it is used. And because this flexible material is in a hard state before printing and has good mechanical properties, it can pass smoothly through the AMS gear transmission system without getting stuck, which means it can adapt well to application scenarios that require frequent material replacement.
[0004] However, the process of making flexible products in this way is actually very complicated and greatly increases the production cost. Moreover, if the problem of flexible material getting stuck in AMS is solved only by increasing the hardness, the flexibility and elasticity of the printed flexible product will deteriorate. In existing research, it was further found that if the material has a high elongation at break, the material will still deform if it encounters a large resistance during the material retraction process; the stretched length will make the material wire diameter thinner and unable to engage effectively. This deformation will cause the material to be stuck in the gear, which is the main reason why the flexible material gets stuck in the AMS transmission gear. Therefore, it is a feasible method to simultaneously control the hardness and elongation at break of the material to develop a flexible material that can be used in AMS but can directly print out flexible products. Summary of the invention
[0005] The present invention proposes a flexible 3D printing material with a double-layer structure and a preparation method thereof. By using an outer layer material with moderate hardness, good tensile strength but low elongation at break to cover an inner layer flexible material with high elongation at break, the 3D printing material can be smoothly replaced in the AMS and the flexible product can be smoothly printed using FDM without additional processing.
[0006] In order to solve the above technical problems, the technical solution of the present invention is:
[0007] A flexible 3D printing material with a double-layer structure, comprising a TPU coating layer and an inner TPU composite material, wherein the TPU coating layer is composed of hard TPU, and the inner TPU composite material is composed of the following components: a flexible TPU and a coupling agent for improving the interfacial bonding strength between the components, and the inner TPU composite material also includes a plasticizer, which is used to improve the overall elongation at break of the material and reduce its hardness, and the plasticizer is one or more of phthalates, terephthalates, succinates or isophthalates.
[0008] The present invention uses a method of coating the hard TPU on the outside of the flexible TPU, so that the 3D printing material is in a state of moderate hardness, good tensile strength and low elongation at break in a normal state, so that the 3D printing material in the AMS can be smoothly replaced; when the 3D printing material is in the FDM print head and is heated for the second time, the inner layer material will mix and react with the outer layer material, changing the performance of the overall material, reducing the hardness of the material, and increasing the elongation at break of the material, thereby realizing the printing of flexible products.
[0009] Specifically, the TPU coating layer will use hard TPU with moderate hardness, good tensile strength and low elongation at break, and the flexible TPU in the inner layer TPU composite material is a common flexible material. The plasticizer added to the inner layer TPU composite material can make the material as a whole soft during the secondary heating and melting process of FDM, which can reduce the overall hardness of the material and increase the elongation at break, thus turning the hard material into a flexible material. The reason for this change is: since the plasticizer molecules are usually small, they can be inserted between the polymer chains (TPU), destroying the original intermolecular forces, thereby reducing the glass transition temperature of the material, making it easier to deform without breaking; and when the plasticizer molecules are inserted between the polymer chains, they will reduce the friction between the polymer chains, making the chain segments easier to slide, thereby improving the ductility and elongation at break of the material.
[0010] Among them, phthalates, terephthalates, and isophthalates: These plasticizers have aromatic ring structures, and they can form hydrogen bonds with polar groups in TPU (such as urea or carbamate groups) through ester groups, thereby improving compatibility with TPU. Succinates: They have longer alkyl chains, which helps to improve the flexibility of the material, and their ester groups can also interact with polar groups in TPU to further enhance compatibility. Therefore, plasticizers are selected from one or more of these four substances.
[0011] Preferably, it is made of the following components in parts by weight:
[0012] Hard TPU: 90~100 parts, flexible TPU: 30~70 parts, coupling agent: 1.5~3 parts, plasticizer: 0.5~2 parts. The use of hard TPU in the coating layer is relatively high, which can ensure that the overall hardness and tensile strength of the material are in a moderate state, so that the double-layer structure material can be smoothly transmitted and changed in the AMS system; the addition of flexible TPU is to give the material sufficient flexibility and elasticity during the FMD printing process, so that it can print soft products; the addition of coupling agent is to improve the interface bonding strength between hard TPU and flexible TPU, to ensure that the two layers of material can be tightly combined in the non-molten state to prevent stratification.
[0013] Preferably, the coupling agent is γ-aminopropyltriethoxysilane. The γ-aminopropyltriethoxysilane molecule contains two different active groups, aminopropyl and silane groups. The aminopropyl group can form hydrogen bonds with polar groups (such as urea or carbamate groups) in TPU, thereby improving the interfacial bonding strength between hard TPU and flexible TPU in TPU composite materials; at the same time, these silane groups can react with hydroxyl groups on the surface of inorganic and organic materials to form stable silicon-oxygen bonds, thereby enhancing interfacial bonding; in summary, under the joint action of hydrogen bonds and silicon-oxygen bonds, the internal connection of the double-layer structure is more firmly established, avoiding the phenomenon of delamination and peeling. It is worth noting that the aminopropyl and ethoxy groups have good compatibility with the polymer chains of TPU, which enables the coupling agent to be effectively dispersed in the TPU matrix; and the improvement of compatibility also makes it easier for plasticizer molecules to enter between TPU chains, making the overall hardness and elongation at break of the material more evenly distributed during the printing process.
[0014] Preferably, the hardness of the hard TPU is 70~75D, and the hardness of the flexible TPU is 85~95A. As a coating layer, the hard TPU needs to have good hardness and tensile strength. The tensile strength of the TPU with a hardness of 70~75D is relatively good, which allows the 3D printing material to pass smoothly through the clamping of the AMS motor and the dragging of the transmission tension, realizing the free color changing function in the AMS. However, the hardness of the hard TPU cannot be too high. If the hardness is too high, the TPU will become very hard, difficult to bend and easy to break. During the wire changing process, the material may get stuck during the transmission process or cause the pipeline to be blocked. If the hardness is too low, it will become a common flexible material and cannot be used in AMS. Similarly, the hardness of the flexible TPU cannot be too low. If it is too low, the final printed product will become too soft and prone to collapse during the printing process.
[0015] Preferably, the inner layer TPU composite material also includes 0.1 to 5 parts of a foaming agent, and the foaming agent is an azo compound. The foaming agent will play a role in the printing process (i.e., the secondary heating and melting process of FDM), which causes bubbles to exist inside the printed material. The bubbles form a porous structure inside the material, which can absorb external forces and allow the material to deform more when stretched. Therefore, when the foamed material is stretched, the bubbles can be deformed and compressed, thereby increasing the elongation at break of the printed material. Moreover, the presence of bubbles can disperse the stress applied to the material. When the material is stretched, the stress will not be concentrated at a certain point, but distributed on the interface between the bubbles and the matrix, which reduces the possibility of material breakage and makes the printed flexible product flexible and elastic.
[0016] It is worth mentioning that if the temperature at which the foaming agent reacts is low, it is very likely that the foaming reaction will occur during the manufacturing stage of the flexible 3D printing material with a double-layer structure, which will lead to uneven pore distribution in the material, and the foaming agent will be difficult to play a role again during subsequent FDM printing; at the same time, the size of the printed material produced is also difficult to control. Therefore, in the present invention, azo compounds such as those with high thermal stability, which can remain stable at high temperatures and rapidly decompose until the decomposition temperature is reached are selected as the foaming agent in this formula. This characteristic makes the foaming agent only work during the secondary heating and melting process of FDM. In this way, the reaction of the foaming agent during the material manufacturing stage is effectively avoided.
[0017] Among them, the inner layer TPU composite material also includes 5 to 10 parts of talcum powder. Talc can improve the fluidity of the TPU composite material in a molten state, making it easier to pass through an extruder or a print head, thereby improving processing efficiency. It is worth mentioning that after adding talcum powder, it will be distributed in the pore structure and matrix, which can improve the stability of the pores of the foamed material and prevent the pores from collapsing or deforming during the cooling process. This is crucial to the dimensional accuracy, surface finish and overall structural integrity of the product after 3D printing, and can ensure that the printed part still maintains good dimensional stability and mechanical properties after cooling.
[0018] Preferably, the TPU coating layer and the inner layer TPU composite material both further include 1 to 10 parts of SOG compatibilizer, which is a polymer formed by glycidyl methacrylate (GMA) grafted onto the main chain of an ethylene-based elastomer. Adding SOG compatibilizer to the inner and outer layer materials can further promote the uniform dispersion of each component and improve the interfacial bonding strength between the materials. This is because the GMA part contains a polar epoxy group, which can interact with the polar groups (such as carbamate groups or ester groups) in TPU through hydrogen bonds or covalent bonds. This interaction enhances the compatibility between the GMA grafted polymer and the TPU matrix. The polyolefin main chain of the SOG compatibilizer is non-polar, and there is a van der Waals force between it and non-polar fillers such as talcum powder. This weak physical force helps to disperse the filler in the polymer matrix. In this way, the GMA grafted polymer is like a bridge, one end of which is connected to the TPU matrix through its polar GMA part, and the other end interacts with the non-polar filler through its non-polar polyolefin main chain. This bridging effect effectively connects two materials of different polarities, reduces interfacial tension, and improves the overall compatibility of the composite material.
[0019] The present invention also provides a method for preparing a flexible 3D printing material with a double-layer structure, comprising the following steps:
[0020] S1: using a plastic granulator to make the TPU coating layer and the inner layer TPU composite material into granules respectively;
[0021] S2: Using a double extrusion structure and a single die molding process, the TPU coating layer particles and the inner layer TPU composite material particles are placed in two single-screw extruders respectively;
[0022] S3: setting the screw speed and processing temperature of the two single-screw extruders, starting the screw extruders, and allowing the molten TPU coating layer and the molten inner layer TPU composite material to flow into the corresponding flow channels of the single-die die respectively; then, in the fusion zone of the die, the molten TPU coating layer is evenly coated on the outside of the molten inner layer TPU composite material, and they are co-extruded at the die outlet to form a double-layer structure material;
[0023] S4: Allow the double-layered flexible 3D printing material to cool and take shape.
[0024] In this way, the flexible 3D printing material of the double-layer structure of the present invention can be manufactured. Through the method of step S3, the hard TPU can well cover the flexible TPU, forming a double-layer structure flexible material with high surface hardness, large tensile strength, low internal hardness and softness. The coupling agent can make the inner and outer layers of TPU better bonded to avoid delamination and peeling.
[0025] Preferably, in step S3, the highest temperature in the single screw machine for extruding the TPU coating layer does not exceed 215°C, and the highest temperature in the single screw machine for extruding the inner layer TPU composite material does not exceed 190°C. Since the TPU material has poor fluidity at lower temperatures, it is necessary to keep a relatively high temperature in the single screw machine. However, it is easy to degrade at too high a temperature, resulting in a decrease in material performance. Therefore, by setting the maximum temperature for extruding the TPU coating layer to not exceed 215°C, it can be ensured that the material has good fluidity in the molten state without degradation; and within this temperature, the viscosity of the TPU coating layer will also be reduced, making it easier to coat the inner layer material. For the inner layer TPU composite material, the extrusion temperature cannot be too high, as too high a temperature will cause the foaming agent to react prematurely, and too low a temperature will also result in poor fluidity, affecting the coating process of the inner and outer layers of TPU. It should be noted that if the temperature of the extruded TPU coating is too high, the high temperature will be transferred to the inner layer of TPU composite material, which will also cause the foaming agent to react prematurely. Therefore, in order to ensure that the foaming agent only works during the FDM printing process, the maximum temperature of the extruded TPU coating should not exceed 215°C.
[0026] Preferably, in step S3, the screw speed of the single screw machine for extruding the TPU coating layer is 400-500 r / min, and the screw speed of the single screw machine for extruding the inner layer TPU composite material is 30-50 r / min. A higher screw speed provides better fluidity, which helps to evenly distribute the hard TPU in the mold and avoid the problem of uneven coating caused by insufficient fluidity. A lower screw speed helps to fully mix the components (such as flexible TPU, coupling agent, plasticizer, etc.) in the inner layer TPU composite material before extrusion to ensure the uniformity and stability of the material. However, too fast a speed may cause the TPU material to be subjected to excessive shear force during the extrusion process, thereby causing thermal degradation of the material and affecting the mechanical properties and durability of the material. Too slow a speed will result in insufficient fluidity of the TPU coating layer, which may not be extruded smoothly, causing the material to be blocked in the extruder; for the inner layer TPU composite material, a low speed may cause uneven mixing of additives such as coupling agents and plasticizers, affecting the performance of the material.
[0027] In summary, such a flexible 3D printing material with a double-layer structure and its preparation method, by covering an inner layer flexible material with a higher elongation at break with an outer layer material with moderate hardness, good tensile strength but lower elongation at break, allows the 3D printing material to be smoothly replaced in the AMS and flexible products can be smoothly printed using FDM without additional processing. DETAILED DESCRIPTION
[0028] It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as there is no conflict between them.
[0029] A flexible 3D printing material with a double-layer structure includes a TPU coating layer and an inner TPU composite material. The component of the TPU coating layer is hard TPU, and the inner TPU composite material is composed of the following components: flexible TPU and a coupling agent for improving the interface bonding strength between the components. The inner TPU composite material also includes a plasticizer. The plasticizer is used to increase the overall elongation at break of the material and reduce its hardness. The plasticizer is one or more of phthalates, terephthalates, succinates or isophthalates.
[0030] The present invention uses a method of coating the hard TPU on the outside of the flexible TPU, so that the 3D printing material is in a state of moderate hardness, good tensile strength and low elongation at break in a normal state, so that the 3D printing material in the AMS can be smoothly replaced; when the 3D printing material is in the FDM print head and is heated for the second time, the inner layer material will mix and react with the outer layer material, changing the performance of the overall material, reducing the hardness of the material, and increasing the elongation at break of the material, thereby realizing the printing of flexible products.
[0031] Specifically, the TPU coating layer will use hard TPU with moderate hardness, good tensile strength and low elongation at break, and the flexible TPU in the inner layer TPU composite material is a common flexible material. The plasticizer added to the inner layer TPU composite material can make the material as a whole soft during the secondary heating and melting process of FDM, which can reduce the overall hardness of the material and increase the elongation at break, thus turning the hard material into a flexible material. The reason for this change is: since the plasticizer molecules are usually small, they can be inserted between the polymer chains (TPU), destroying the original intermolecular forces, thereby reducing the glass transition temperature of the material, making it easier to deform without breaking; and when the plasticizer molecules are inserted between the polymer chains, they will reduce the friction between the polymer chains, making the chain segments easier to slide, thereby improving the ductility and elongation at break of the material.
[0032] Among them, phthalates, terephthalates, and isophthalates: These plasticizers have aromatic ring structures, and they can form hydrogen bonds with polar groups in TPU (such as urea or carbamate groups) through ester groups, thereby improving compatibility with TPU. Succinates: They have longer alkyl chains, which helps to improve the flexibility of the material, and their ester groups can also interact with polar groups in TPU to further enhance compatibility. Therefore, plasticizers are selected from one or more of these four substances.
[0033] Preferably, it is made of the following components in parts by weight:
[0034] Hard TPU: 90~100 parts, flexible TPU: 30~70 parts, coupling agent: 1.5~3 parts, plasticizer: 0.5~2 parts. The use of hard TPU in the coating layer is relatively high, which can ensure that the overall hardness and tensile strength of the material are in a moderate state, so that the double-layer structure material can be smoothly transmitted and changed in the AMS system; the addition of flexible TPU is to give the material sufficient flexibility and elasticity during the FMD printing process, so that it can print soft products; the addition of coupling agent is to improve the interface bonding strength between hard TPU and flexible TPU, to ensure that the two layers of material can be tightly combined in the non-molten state to prevent stratification.
[0035] Preferably, the coupling agent is γ-aminopropyltriethoxysilane. The γ-aminopropyltriethoxysilane molecule contains two different active groups, aminopropyl and silane groups. The aminopropyl group can form hydrogen bonds with polar groups (such as urea or carbamate groups) in TPU, thereby improving the interfacial bonding strength between the hard TPU and the flexible TPU in the TPU composite material; at the same time, the silane group can react with the hydroxyl groups on the surface of inorganic and organic materials to form stable silicon-oxygen bonds, thereby enhancing interfacial bonding; in summary, under the combined action of hydrogen bonds and silicon-oxygen bonds, the internal connection of the double-layer structure is made more firm, avoiding the phenomenon of delamination and peeling.
[0036] It is worth noting that the aminopropyl and ethoxy groups have good compatibility with the polymer chains of TPU, which enables the coupling agent to be effectively dispersed in the TPU matrix; and the improvement in compatibility also makes it easier for plasticizer molecules to enter between TPU chains, making the overall hardness and elongation at break of the material more evenly distributed during the printing process.
[0037] Preferably, the hardness of hard TPU is 70~75D, and the hardness of flexible TPU is 85~95A. As a coating layer, hard TPU needs to have good hardness and tensile strength. TPU with a hardness of 70~75D has relatively good tensile strength, which allows the 3D printing material to pass through the AMS motor clamping and transmission tension drag smoothly, and realize the free color change function in AMS. However, the hardness of hard TPU cannot be too high. If the hardness is too high, the TPU will become very hard, difficult to bend and easy to break. During the wire changing process, the material may get stuck during the transmission process or cause the pipeline to be blocked. If the hardness is too low, it will become a common flexible material and cannot be used in AMS. Similarly, the hardness of flexible TPU cannot be too low. If it is too low, the final printed product will become too soft and prone to collapse during the printing process.
[0038] Preferably, the inner layer TPU composite material also includes 0.1 to 5 parts of a foaming agent, which is an azo compound. The foaming agent will play a role in the printing process (i.e., the secondary heating and melting process of FDM), which causes bubbles to exist inside the printed material. The bubbles form a porous structure inside the material, which can absorb external forces and allow the material to deform more when stretched. Therefore, when the foamed material is stretched, the bubbles can be deformed and compressed, thereby increasing the elongation at break of the printed material. Moreover, the presence of bubbles can disperse the stress applied to the material. When the material is stretched, the stress will not be concentrated at a certain point, but distributed on the interface between the bubbles and the matrix, which reduces the possibility of material breakage and makes the printed flexible products flexible and elastic.
[0039] It is worth mentioning that if the temperature at which the foaming agent reacts is low, it is very likely that the foaming reaction will occur during the manufacturing stage of the flexible 3D printing material with a double-layer structure, which will lead to uneven pore distribution in the material, and the foaming agent will be difficult to play a role again during subsequent FDM printing; at the same time, the size of the printed material produced is also difficult to control. Therefore, in the present invention, azo compounds such as those with high thermal stability, which can remain stable at high temperatures and rapidly decompose until the decomposition temperature is reached are selected as the foaming agent in this formula. This characteristic makes the foaming agent only work during the secondary heating and melting process of FDM. In this way, the reaction of the foaming agent during the material manufacturing stage is effectively avoided.
[0040] The inner layer TPU composite material also includes 5 to 10 parts of talcum powder, which can improve the fluidity of the TPU composite material in a molten state, making it easier to pass through an extruder or a print head, thereby improving processing efficiency.
[0041] It is worth mentioning that after adding talcum powder, it will be distributed in the pore structure and matrix, which can improve the stability of the pores of the foamed material and prevent the pores from collapsing or deforming during the cooling process. This is crucial to the dimensional accuracy, surface finish and overall structural integrity of the product after 3D printing, and can ensure that the printed parts still maintain good dimensional stability and mechanical properties after cooling.
[0042] Preferably, the TPU coating layer and the inner layer TPU composite material also include 1 to 10 parts of SOG compatibilizer, which is a polymer formed by glycidyl methacrylate (GMA) grafted onto the main chain of ethylene elastomer. Adding SOG compatibilizer to the inner and outer layer materials can further promote the uniform dispersion of each component and improve the interfacial bonding strength between the materials. This is because the GMA part contains a polar epoxy group, which can interact with the polar groups (such as carbamate groups or ester groups) in TPU through hydrogen bonds or covalent bonds. This interaction enhances the compatibility between the GMA grafted polymer and the TPU matrix. The polyolefin main chain of the SOG compatibilizer is non-polar, and there is a van der Waals force between it and non-polar fillers such as talcum powder. This weak physical force helps to disperse the filler in the polymer matrix. In this way, the GMA grafted polymer is like a bridge, one end of which is connected to the TPU matrix through its polar GMA part, and the other end interacts with the non-polar filler through its non-polar polyolefin main chain. This bridging effect effectively connects two materials of different polarities, reduces interfacial tension, and improves the overall compatibility of the composite material.
[0043] The present invention also provides a method for preparing a flexible 3D printing material with a double-layer structure, comprising the following steps:
[0044] S1: using a plastic granulator to make the TPU coating layer and the inner layer TPU composite material into granules respectively;
[0045] S2: Using a double extrusion structure and a single die molding process, the TPU coating layer particles and the inner layer TPU composite material particles are placed in two single-screw extruders respectively;
[0046] S3: setting the screw speed and processing temperature of the two single-screw extruders, starting the screw extruders, and allowing the molten TPU coating layer and the molten inner layer TPU composite material to flow into the corresponding flow channels of the single-die die respectively; then, in the fusion zone of the die, the molten TPU coating layer is evenly coated on the outside of the molten inner layer TPU composite material, and they are co-extruded at the die outlet to form a double-layer structure material;
[0047] S4: Allow the double-layered flexible 3D printing material to cool and take shape.
[0048] In this way, the flexible 3D printing material of the double-layer structure of the present invention can be manufactured. Through the method of step S3, the hard TPU can well cover the flexible TPU, forming a double-layer structure flexible material with high surface hardness, large tensile strength, low internal hardness and softness. The coupling agent can make the inner and outer layers of TPU better bonded to avoid delamination and peeling.
[0049] Preferably, in step S3, the highest temperature in the single screw machine for extruding the TPU coating layer does not exceed 215°C, and the highest temperature in the single screw machine for extruding the inner layer TPU composite material does not exceed 190°C. Since the TPU material has poor fluidity at lower temperatures, it is necessary to keep a relatively high temperature in the single screw machine, but it is easy to degrade at too high a temperature, resulting in a decrease in material performance. Therefore, by setting the maximum temperature for extruding the TPU coating layer to not more than 215°C, it can be ensured that the material has good fluidity in a molten state without degradation; and within this temperature, the viscosity of the TPU coating layer will also be reduced, making it easier to coat the inner layer material. For the inner layer TPU composite material, the extrusion temperature cannot be too high, as too high a temperature will cause the foaming agent to react prematurely, and too low a temperature will also result in poor fluidity, affecting the coating process of the inner and outer layers of TPU.
[0050] It should be noted that if the temperature of the extruded TPU coating is too high, the high temperature will be transferred to the inner layer of TPU composite material, which will also cause the foaming agent to react prematurely. Therefore, in order to ensure that the foaming agent only works during the FDM printing process, the maximum temperature of the extruded TPU coating should not exceed 215°C.
[0051] Preferably, in step S3, the screw speed of the single screw machine for extruding the TPU coating layer is 400-500r / min, and the screw speed of the single screw machine for extruding the inner layer TPU composite material is 30-50r / min. A higher screw speed provides better fluidity, which helps to evenly distribute the hard TPU in the mold and avoid the problem of uneven coating caused by insufficient fluidity. A lower screw speed helps to fully mix the components (such as flexible TPU, coupling agent, plasticizer, etc.) in the inner layer TPU composite material before extrusion to ensure the uniformity and stability of the material. However, too fast a speed may cause the TPU material to be subjected to excessive shear force during the extrusion process, thereby causing thermal degradation of the material and affecting the mechanical properties and durability of the material. Too slow a speed will result in insufficient fluidity of the TPU coating layer, which may not be extruded smoothly, causing the material to be blocked in the extruder; for the inner layer TPU composite material, a low speed may cause uneven mixing of additives such as coupling agents and plasticizers, affecting the performance of the material.
[0052] In summary, such a flexible 3D printing material with a double-layer structure and its preparation method, by covering an inner layer flexible material with a higher elongation at break with an outer layer material with moderate hardness, good tensile strength but lower elongation at break, allows the 3D printing material to be smoothly replaced in the AMS and flexible products can be smoothly printed using FDM without additional processing.
[0053] To verify the effect, the AMS device printed with FDM was tested.
[0054] Example 1: 90 parts of hard TPU, 50 parts of flexible TPU, 0.5 parts of terephthalate, 0.5 parts of succinate, 1.5 parts of γ-aminopropyltriethoxysilane, 1 part of azo compound, 5 parts of talc, 3 parts of SOG compatibilizer. The hardness of hard TPU is 70D, and the hardness of flexible TPU is 95A. The above materials are prepared into 1.75mm diameter wire, wherein the highest temperature in the single screw machine for extruding the TPU coating layer is 215℃, and the screw speed is 400r / min, and the highest temperature in the single screw machine for extruding the inner layer TPU composite material is 180℃, and the screw speed of the single screw machine is 30r / min.
[0055] The processed 1.75mm straight wire has a length of 1000mm. Under a pulling force of 12Nd, the material elongates to 108mm and the elongation is 8%. After the standard processing test of 3D printing splines, the tensile strength of the material is 28Mpa~29Mpa, the elongation at break is 410~430%, and the hardness test is 51~52D. The printed product has good flexibility.
[0056] Example 2: Hard TPU: 95 parts, flexible TPU: 60 parts, phthalate: 0.1 parts, terephthalate: 0.3 parts, succinate 0.2 parts, γ-aminopropyl triethoxysilane: 2 parts, azo compound 2 parts, talc 5 parts, SOG compatibilizer 3 parts. The hardness of the hard TPU is 70D, and the hardness of the flexible TPU is 95A. The above materials are prepared into 1.75mm diameter wire, wherein the highest temperature in the single screw machine for extruding the TPU coating layer is 215℃, the screw speed is 400r / min, the highest temperature in the single screw machine for extruding the inner layer TPU composite material is 185℃, and the screw speed of the single screw machine is 45r / min.
[0057] The same 1.75mm diameter printing wire is used with a length of 1000mm. Under a pulling force of 12N, the material elongates to 106mm and the elongation is 6%. After the 3D printing process to prepare the standard sample test, the tensile strength of the material is 30~32Mpa, the elongation at break is 430~460%, and the hardness test is 50~52D. The printed product has good flexibility.
[0058] Comparative Example: Compared with Example 2, only the treatment without adding phthalate, terephthalate and succinate was performed.
[0059] The same 1.75mm diameter printing wire length is 1000mm. Under the pulling force of 12N, the material elongation length is 103mm, and the elongation is 3%. After the 3D printing process to prepare the standard sample test, the tensile strength of the material is 43~44Mpa, the elongation at break is 250~300%, and the hardness test is 60~62D. The printed product has lost its flexibility.
[0060] According to the above scheme, the AMS equipment for FDM printing was tested.
[0061] Example 1: AMS successfully passed the test, and it was best to change colors and materials more than 1,000 times without any problems; flexible products of different colors can be printed smoothly;
[0062] Example 2: AMS successfully passed the test, and it was best to change colors and materials more than 1,000 times without any problems; flexible products of different colors can be printed smoothly;
[0063] Comparative example: In AMS, the material was obviously stuck in the transmission pipeline; the printed product did not meet the requirements of flexible products and had poor flexibility.
[0064] In summary, it can be seen that the solution of the present invention can realize the material change in the AMS system and can smoothly print flexible products of different colors. The rational use of plasticizer plays a key role. Failure to add plasticizer will cause the material to lose a certain degree of flexibility, and the material may get stuck in the transmission channel during the process of clamping and driving the pulling force of the AMS motor.
[0065] It is apparent to those skilled in the art that various changes, modifications, substitutions and variations may be made to these embodiments without departing from the principles and spirit of the invention, and the changes still fall within the protection scope of the invention.
Claims
1. A flexible 3D printing material with a double-layer structure, comprising a TPU coating layer and an inner layer of TPU composite material, wherein the component of the TPU coating layer is hard TPU, and the inner layer of TPU composite material is composed of the following components: Flexible TPU and a coupling agent for improving the interfacial bonding strength between the components, characterized in that the inner layer TPU composite material also includes a plasticizer, the plasticizer is used to improve the overall elongation at break of the material and reduce its hardness, and the plasticizer is one or more of phthalates, terephthalates, succinates or isophthalates; Made of the following components in parts by weight: hard TPU: 90-100 parts, flexible TPU: 30-70 parts, coupling agent: 1.5-3 parts, plasticizer: 0.5-2 parts; The coupling agent is γ-aminopropyltriethoxysilane; The hardness of the hard TPU is 70-75D, and the hardness of the flexible TPU is 85-95A.
2. The flexible 3D printing material with a double-layer structure according to claim 1, characterized in that: The inner layer TPU composite material also includes 0.1 to 5 parts of a foaming agent, and the foaming agent is an azo compound.
3. The flexible 3D printing material with a double-layer structure according to claim 2, characterized in that: The inner layer TPU composite material also includes 5 to 10 parts of talc.
4. The flexible 3D printing material with a double-layer structure according to claim 3, characterized in that: The TPU coating layer and the inner layer TPU composite material both further include 1 to 10 parts of SOG compatibilizer, and the SOG compatibilizer is a polymer formed by grafting glycidyl methacrylate (GMA) onto the main chain of ethylene elastomer.
5. A method for preparing a flexible 3D printing material with a double-layer structure, characterized in that: The method for preparing a flexible 3D printing material with a double-layer structure as claimed in any one of claims 1 to 4 comprises the following steps: S1: using a plastic granulator to make the TPU coating layer and the inner layer TPU composite material into granules respectively; S2: Using a double extrusion structure and a single die molding process, the TPU coating layer particles and the inner layer TPU composite material particles are placed in two single-screw extruders respectively; S3: setting the screw speed and processing temperature of the two single-screw extruders, starting the screw extruders, and allowing the molten TPU coating layer and the molten inner layer TPU composite material to flow into the corresponding flow channels of the single-die die respectively; then, in the fusion zone of the die, the molten TPU coating layer is evenly coated on the outside of the molten inner layer TPU composite material, and they are co-extruded at the die outlet to form a double-layer structure material; S4: Allow the double-layered flexible 3D printing material to cool and take shape.
6. The method for preparing a flexible 3D printing material with a double-layer structure according to claim 5, characterized in that: In step S3, the highest temperature in the single screw machine for extruding the TPU coating layer does not exceed 215°C, and the highest temperature in the single screw machine for extruding the inner layer TPU composite material does not exceed 190°C.
7. The method for preparing a flexible 3D printing material with a double-layer structure according to claim 6, characterized in that: In the step S3, the screw speed of the single screw machine for extruding the TPU coating layer is 400-500 r / min, and the screw speed of the single screw machine for extruding the inner layer TPU composite material is 30-50 r / min.
Citation Information
Patent Citations
Co-extrusion wood-plastic composite material and preparation method thereof
CN110216959A
3D printing wire rod and preparation method and application thereof
CN115449215A
Cited By
Gilding colorful 3D printing material prepared based on multiple runners and preparation method of gilding colorful 3D printing material
CN121492313A